ANALISIS NILAI-NILAI ISLAM DALAM BUDAYA OR-GANISASI PADA PT. SEEMOUNT GARDEN SEJAHTERA - Daud Haekal Hawari; Lathiefa Rusli (Islamic Business and Management Journal, 2019)
Some companies in Indonesia apply Islamic values to the organization, one of them is PT. Seemount Garden Sejahtera which has Islamic values and products. There are problems at PT. Seemount Garden Sejahtera in understanding among employees challenges the form of Islamic values that are applied in the organizational culture of this company because the form of these values has not been fully documented visually so that the employee does not yet know the form of Islamic values applied by the company so far. In applying Islamic values in organizational culture researchers also want to know what strategies are applied to organizational culture at PT. Seemount Garden Sejahtera. From this research, it can be concluded that employees at PT. Seemount Garden Sejahtera has the answer that they apply and develop Islamic values in organizational culture that has the form of Al-Itqan, At-Tanafus, Ta'awun, Jama'ah and halal. From the results of interviews conducted to employees at PT. Seemount Garden Sejahtera the author has a conclusion on the strategies used by this company. Of the four strategies of engagement, namely aggressiveness, peace, corrosiveness, and indoctrinative the employees of this company answered that the peaceful strategy was the strategy used in this company. We can see this peaceful strategy in the answers of the employees who revealed that the peaceful strategy is a strategy that is effective and superior in dealing with employees because employees at this company still have close family relationships so that the company director does not set rules flexibly and can be accepted by employee. From the employee reaction to organizational culture, three out of five respondents answered that Selective Reinterpretation is a form of employee reaction to the organizational culture of this company, because the employees of the company obey suitable regulations and do not comply with inappropriate regulations, if there are new regulations used Employee companies prefer the old rules to be more suited to them than running new regulations that are not suitable.